Peran Orang Tua dalam Mendukung Pembentukan Karakter Islami pada Generasi Z - Samin; Abdul Kamil; Rijal Azman; Rozak Umar Wibowo (Tashfiyatuna: Jurnal Pendidikan Keislaman, 2023)
This study aims to explore the role of parents and teachers in shaping the Islamic character of Generation Z students and emphasizes the importance of collaboration between religious education at home and at school. The research uses a qualitative approach with an exploratory descriptive design. Data were collected through in-depth interviews with parents and Islamic Religious Education (PAI) teachers, group discussions with students, and observations of religious education activities. The results show that parents play an important role in instilling Islamic values through appropriate parenting, although they face challenges such as limited time and knowledge. Meanwhile, PAI teachers implement learning strategies suited to the characteristics of Generation Z, but still encounter challenges in strengthening students’ Islamic character. Collaboration between parents and schools supports the effectiveness of religious education, although several obstacles remain. Therefore, stronger communication, increased cooperation, and training programs for parents are needed to support children’s religious education.